Social Business Hybrids: Demand Externalities, Competitive Advantage, and Growth Through Diversification - Fosfuri, Andrea; Giarratana, Marco S.; Roca, Esther (Organization Science, 2016)
Organization scholars have recently studied the internal challenges and opportunities faced by companies that combine business and social logics (i.e., social business hybrids). By adopting a demand-side perspective, this paper addresses the implications of hybridity for strategic choices with products and businesses by focusing on the role of social business hybrids’ customers. In the conceptual framework, social identity theory explains how hybridity generates both positive and negative demand-side externalities. Thus, hybridity can be a source of competitive advantage in the marketplace, but also create hurdles to firms’ ability to scale up their business. Diversification represents a potential choice that simultaneously generates growth, preserves hybridity, and avoids negative demand-side externalities. This paper analyzes the optimal type, timing, and scope of such diversification.